Silence in the land of logos - Montiglio, Silvia, 1960- (Princeton University Press, 2000)
In ancient Greece, the spoken word connoted power, whether in the free speech accorded to citizens or in the voice of the poet, whose song was thought to know no earthly bounds. But how did silence fit into the mental framework of a society that valued speech so highly? Here Silvia Montiglio provides the first comprehensive investigation into silence as a distinctive and meaningful phenomenon in archaic and classical Greece. Arguing that the notion of silence is not a universal given but is rather situated in a complex network of associations and values, Montiglio seeks to establish general pr.